PERAN PARIWISATA DALAM MENINGKATKAN PERTUMBUHAN EKONOMI MASYARAKAT - Elsa, Elsa (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2016)
This paper to see how tourism can provide stimulus to economic growth. In tourism the interaction between tourists and local communities so as to enhance economic activities such as revenues, business opportunities, employment opportunities and reduce unemployment or poverty erodes. So, it can be explained that between the tourism sector and the economy is directly proportional, if the tourism sector increases, people's income also increased. Conversely, if the tourism sector are declining, people's income also declined. Tourism is the engine driving and driving the creation of creativity of the community in an effort to improve the lives. Problems that develop in the tourism sector is the lack of knowledge and understanding on tourism, a reference to incomplete about the tourist places (socialization of local government is still not satisfactory), and stepping are not implemented (safe, orderly, clean, cool, beautiful, welcoming, and memories) in the tourism sector. Therefore, to overcome the problem of tourism is needed awareness by government and the community to develop and explore the potential of tourism as an effort to increase the standard of living and the quality of the people in the area. Efforts are underway to explore the potential of travel may include human resource development, implementation stepping, as well as the improvement of facilities and infrastructures. It can boost the high interest of tourists to visit the tourist destination so that not only the public economy are growing, but the skill and creativity of the community also increased.Keywords: Tourism, Economic Growth.